CBD enhances the cognitive score of adolescent rats prenatally exposed to THC and fine-tunes relevant effectors of hippocampal plasticity - Valentina Castelli; Gianluca Lavanco; Cesare D'Amico; Salvatore Feo; Giuseppe Tringali; Giuseppe Tringali; Martin Kuchar; Martin Kuchar; Carla Cannizzaro; Anna Brancato (Frontiers Media S.A., 2023)
Introduction: An altered neurodevelopmental trajectory associated with prenatal exposure to ∆-9-tetrahydrocannabinol (THC) leads to aberrant cognitive processing through a perturbation in the effectors of hippocampal plasticity in the juvenile offspring. As adolescence presents a unique window of opportunity for "brain reprogramming", we aimed at assessing the role of the non-psychoactive phytocannabinoid cannabidiol (CBD) as a rescue strategy to temper prenatal THC-induced harm.Methods: To this aim, Wistar rats prenatally exposed to THC (2 mg/kg s.c.) or vehicle (gestational days 5-20) were tested for specific indexes of spatial and configural memory in the reinforcement-motivated Can test and in the aversion-driven Barnes maze test during adolescence. Markers of hippocampal excitatory plasticity and endocannabinoid signaling-NMDAR subunits NR1 and 2A-, mGluR5-, and their respective scaffold proteins PSD95- and Homer 1-; CB1R- and the neuromodulatory protein HINT1 mRNA levels were evaluated. CBD (40 mg/kg i.p.) was administered to the adolescent offspring before the cognitive tasks.Results: The present results show that prenatal THC impairs hippocampal memory functions and the underlying synaptic plasticity; CBD is able to mitigate cognitive impairment in both reinforcement- and aversion-related tasks and the neuroadaptation of hippocampal excitatory synapses and CB1R-related signaling.Discussion: While this research shows CBD potential in dampening prenatal THC-induced consequences, we point out the urgency to curb cannabis use during pregnancy in order to avoid detrimental bio-behavioral outcomes in the offspring.